Challenges in lung transplantation (Swiss Medical Weekly, 2011)
Lung transplantation is an established therapy for end-stage pulmonary disorders in selected patients without significant comorbidities. The particular constraints associated with organ transplantation from deceased donors involve specific allocation rules in order to optimise the medical efficacy of the procedure. Comparison of different policies adopted by national transplant agencies reveals that an optimal and unique allocation system is an elusive goal, and that practical, geographical and logistic parameters must be taken into account. A solution to attenuate the imbalance between the number of lung transplant candidates and the limited availability of organs is to consider marginal donors. In particular, assessment and restoration of gas exchange capacity ex vivo in explanted lungs is a new and promising approach that some lung transplant programmes have started to apply in clinical practice. Chronic lung allograft dysfunction, and especially bronchiolitis obliterans, remains the major medium- and long-term problem in lung transplantation with a major impact on survival. Although there is to date no cure for established bronchiolitis obliterans, new preventive strategies have the potential to limit the burden of this feared complication. Unfortunately, randomised prospective studies are infrequent in the field of lung transplantation, and data obtained from larger studies involving kidney or liver recipients are not always relevant for this purpose.